Pengembangan Motif Pohon Pinus Jenis Densiflora Pada Aplikasi Batik Berbasis Web Dengan Metode Lindenmayer-system (l-system) - Fikri Reksa Maulana; Purba Daru Kusuma; Rumani M (eProceedings of Engineering, 2019)
Abstrak Salah satu warisan budaya terbesar dan terbaik di Indonesia adalah batik. Salah satu cara untuk melestarikan batik adalah dengan mengekplorasi pola baru untuk dijadikan batik. Pola batik dapat diambil dari bentuk benda, tumbuhan, bahkan berbentuk hewan. Oleh karena itu pada penelitian ini, pola yang dijadikan batik adalah pola dari tumbuhan pinus kelompok Densiflora. Pola batik dikembangkan menggunakan metode L-System. Metode L-System dipilih karena metode tersebut banyak digunakan untuk memodelkan tumbuhan atau obyek-obyek yang memiliki sifat mirip dengan tumbuhan yaitu memanjang,bercabang dan berhenti tumbuh. Selain menggunakan L-system, metode Random walk juga digunakan dalam pengembangan motif batik ini. Random walk digunakan untuk menambah unsur stokastik pada pertumbuhan pohon pinus. Selanjutnya, model yang dikembangkan diimplementasikan ke dalam aplokasi pengembangan motif batik berbasis web. One of the biggest and best cultural heritage in Indonesia is batik. One way to preserve batik is to explore new patterns for making batik. Batik patterns can be taken from objects, plants, and even animals. Therefore, in this study, the pattern used as batik is a pattern of pine plants in the Densiflora group. Batik patterns are developed using the L-System method. The L-System method is chosen because the method is widely used to model plants or objects that have properties similar to plants which are elongated, branched and stop growing. In addition to using the L-system, the Random walk method is also used in the development of this batik motif. Random walk is used to add stochastic elements to pine tree growth. Furthermore, the model developed was implemented into the aplocation of the development of web-based batik motifs. Kata kunci: L-Systems, WEB, Application, Web-Based, Batik, Pinus Abstract Batik is one of the biggest and best cultural heritage. One way to preserve batik is to explore new patterns. Batik patterns can be taken from objects, plants, and even animals. Therefore, in this study, the pattern that is used as batik is a pattern of pine plants in the Densiflora group. Batik patterns are developed by using the L-System method. The L-System method is chosen because the method is widely used to modeling the plants or objects that have properties similar to plants which are elongated, branched and stop growing. In addition to using the L-system, the Random walk method is also used in the development of this batik patterns. Random walk is used to add stochastic elements to pine tree growth. Furthermore, the developed model was implemented into the web-based batik pattern application. . Keywords: Simulator, Driving, Input, System